Menopausal women – what are their partners like?Part II. Partners and sexual relations - Jakiel, Grzegorz; Pilewska-Kozak, Anna B.; Łepecka-Klusek, Celina; Tkaczuk-Włach, Joanna; Syty, Kinga (Menopause Review/Przegląd Menopauzalny, 2009)
A review of partnership and sexual relations between man and his menopausal woman was done. The main cause of difficulties in the bonds of emotions in the perimenopausal woman’s family is the lesser interest in sex and the mid-life crisis of her partner. The partner’s nervousness, irritability, memory deterioration, moodiness, and symptoms of depression are only some of the symptoms of senescence of man; moreover, sometimes suspiciousness and jealousy about younger men is observed. The main difficulty in the relations between a woman and her older man is the problem of intimate life. Erectile disorders and woman’s aversion to sexual activity are frequently observed in this period and result in decreased frequency of sexual intercourses. Cultural, religious and social factors may disturb the sexual relations of men. Higher socioeconomic status is connected with increased sexual drive in men. Pharmacotherapy helps many of them to overcome erectile disorder. Then, the woman who has come to accept abstinence is expected to resume sexual activity, at times overcoming her biological difficulties. In these times the bonds of emotions and openness to one’s partner’s needs are the stimuli of sexual initiation, rather than his attractiveness. Sexual activity in older age is the natural need of woman and man. Fighting and overcoming the biological barriers concerning sexual life before a marital/relationship crisis occurs should be the aim of modern medicine.